Fiscal Prevention of Counterfeit Cosmetics Imports: The Impact of Consumption Tax on Luxury Cosmetics (The Case of Russia and China) - Viktoriia A. KORETSKAIA-GARMASH; Elena V. IADRENNIKOVA (Communications of International Proceedings, 2020)
Cosmetics and makeup are the goods commonly associated with a healthy lifestyle and beauty as they are used to highlight one's best features and to hide imperfections. These goods are consumed by all population groups who anticipate to effect an agreeable visual impression. The demand for cosmetics is heavily influenced by users' comments and opinions on social media concerning the quality and effects of different products as well as advertising campaigns in mass media and the price levels. This study tests the hypothesis that the introduction of excise duties on luxury cosmetics in Russia will create a protective barrier against the imports of counterfeit goods. We use the case of China to show that consumption tax on cosmetics can be quite effective in this respect. The study provides an overview of the global trends in the cosmetics market and taxation of luxury cosmetics in China. The sales of cosmetics of mass market and luxury brands are considered. The volume and structure of the imports of cosmetics to Russia are analyzed. The conclusion is drawn concerning the potential of excise duties on luxury cosmetics in Russia in combatting the imports of counterfeit products.
Keywords: Consumption Tax; Excise Duties; Cosmetics; Luxury Cosmetics; Mass Market Cosmetics; China; Russia